Estudo sobre Educação Ambiental Diferenciada na comunidade quilombola do Campo Novo, Tracuateua-Pa - ROSA, Maria Tatiane Araújo da (2024)
Critical Environmental Education aims to transform thinking through engagement in the form of attitudes and actions that are part of building a different kind of society. It is culturally differentiated when planned from an intercultural perspective and carried out for and with indigenous peoples, quilombolas and/or traditional communities. This work had its theoretical and epistemological foundation built from the analysis of bibliographic material, in order to carry out a survey with managers and teachers from the three schools that serve the Campo Novo Quilombola Community, Tracuateua - PA. Interviews were conducted with them, and the PPPs of the same educational institutions were analyzed. In addition, a study was carried out on the Flour without Firewood Project, which uses biogas to make flour in the community. Managers and teachers showed interest to participate in interactive activities that join the school and the community. So, a teaching sequence was planned, involving the biogas process and the production of energy by microorganisms. It is thought that, with the continuity of the Action Plan that emerges from this work, there may in fact be a re-signification of ideas and values, strengthening the students' links with the Quilombola Community.